Evaluation Study on Short Stay Homes for Women and Girls - Planning Commission (Planning Commission, 1999)
The scheme of Short Stay Homes for Women and Girls was launched in 1969 to provide temporary shelter to women and girls, who are in moral danger due to family problems, violence at homes, mental strain and other causes. The scheme is designed to provide a packages of services like medical care, psychiatric treatment, case work services, occupational therapy, educational -cum- vocational training, recreation facilities and rehabilitation of inmates. At the instance of the Department of Women and Child Development, Ministry of Human Resource Development, PEO undertook the study to evaluate the performance and functioning of Short Stay Homes. The study was also required to reflect on the relevant issues relating to the design and implementation of the scheme and to suggest modifications for a more efficient and cost effective intervention.
Programme Evaluation Organisation Planning Commission Government of India New Delhi